Parasites and wildlife in a changing world: The vector-host- pathogen interaction as a learning case. (August 2019) - Rizzoli, Annapaola; Tagliapietra, Valentina; Cagnacci, Francesca; Marini, Giovanni; Arnoldi, Daniele; Rosso, Fausta; Rosà, Roberto
Abstract: In the Anthropocene context, changes in climate, land use and biodiversity are considered among the most important anthropogenic factors affecting parasites-host interaction and wildlife zoonotic diseases emergence. Transmission of vector borne pathogens are particularly sensitive to these changes due to the complexity of their cycle, where the transmission of a microparasite depends on the interaction between its vector, usually a macroparasite, and its reservoir host, in many cases represented by a wildlife vertebrate. The scope of this paper focuses on the effect of some major, fast-occurring anthropogenic changes on the vectorial capacity for tick and mosquito borne pathogens. Specifically, we review and present the latest advances regarding two emerging vector-borne viruses in Europe: Tick-borne encephalitis virus (TBEV) and West Nile virus (WNV). In both cases, variation in vector to host ratio is critical in determining the intensity of pathogen transmission and consequently infection hazard for humans. Forecasting vector-borne disease hazard under the global change scenarios is particularly challenging, requiring long term studies based on a multidisciplinary approach in a One-Health framework. Highlights: In the Anthropocene changes in parasite-host interaction are accelerated. Megatrends in climate, land use and biodiversity loss drive wildlife zoonotic diseases emergence. Vector borne diseases are on the rise. Changes in vectorial capacity need to be quantified. Innovative tools nowadays are available to improve surveillance and risk modelling.